Empowering tomorrow’s scholars: shifting exam-oriented to insightful learning among foundation students - Tuan Muda, Tuan Nor Shazni; Yahya, Ezny; Bahrom, Suhaila; Hisham, Balqis; Mohd Khalid, Farah Zawani (Centre for Foundation Studies (CFS), IIUM, 2024)
An exam-oriented approach predominantly drives the current educational landscape, often limiting students' intellectual curiosity and critical thinking abilities. This paper proposes a paradigm shift towards insightful learning, particularly for foundation students, to foster a more profound and holistic educational experience. By integrating innovative pedagogical strategies that emphasise understanding, creativity, and application of knowledge, this paper aims to cultivate scholars who are not only aiming at passing exams but are also equipped with the skills necessary for lifelong learning and problem-solving. Key methodologies include role play and cinematic learning, which collectively promote a deeper engagement with the material. A purposive sampling technique was used to select a sample of 184 students taking Understanding Islam II from CFS IIUM for this study. The data were analysed using both descriptive and inferential analysis using SPSS. Preliminary results from the study indicate significant improvements in students’ understanding and motivation towards learning. The paper concludes with recommendations for educators to support the transition towards an education system that values and nurtures insightful learning, ultimately empowering students to become innovative and adaptive thinkers prepared for future challenges.